Foundations for a disequilibrium theory of the business cycle : qualitative analysis and quantitative assessment - Chiarella, Carl (Cambridge University Press, 2005)
"Building on The Dynamics of Keynesian Monetary Growth by Chiarella and Flaschel (2000), this book is a key contribution to business cycle theory, setting out a disequilibrium approach with gradual adjustments of the key macroeconomic variables. Its analytic study of a deterministic model of economic activity, inflation and income distribution integrates elements in the tradition of Keynes, Metzler and Goodwin. After a qualitative analysis of the basic feedback mechanisms, the authors calibrate the KMG model to the stylized facts of the business cycle in the US economy, and then undertake a detailed numerical investigation of the local and global dynamics generated by the model.